Mathematical Model For Quantitative Analysis Of Acidogenic Performance Under Microaeration Condition In Anaerobic Vinasse Treatment - Budianto, Gregorius Indra Prima; Sudjarwo, Wisnu Arfian Anditya (Jurnal Riset Teknologi Pencegahan Pencemaran Industri, 2020)
Vinase anaerobic treatment is a one alternative process to treating vinasse. Microaeration is a one of process modification in anaerobic vinasse digestion that can improve the acidogenic performance. In this paper presents the influence microaeration in anaerobic vinasse treatment in kinetics aspect. The kinetics aspect was develop to approach and quantifying the effect of microaeration in anaerobic vinasse treatment systematically. Extract of cow dung was used as inoculums and vinasse 100 ppm as a substrate. Laboratory experiments using 4L vertical reactor (UASB) was conducted in 28 days and performed in batch recirculation mode. During the experiment, dosing air in different concentrations was injected in the slurry phase into different anaerobic digesters once a day. The variation of air concentrations are 0 L air/L feed; 0.5 L air/L feed; and 100 L air/L feed. As the result, the addition of 0.5 Lair/L feed could increase biodegradability (k=-5.7239) and accelerate acidogenesis phase (μm1=2.03/day) that can be proven by the percentage of VS removal reaching up to 77% and cuts the lag phase (λ=1.028 days) and HRT making it shorter.